2012
DOI: 10.1093/ejcts/ezs083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of residual regurgitation after aortic valve replacement

Abstract: Postoperative residual AR >1/4 is an independent predictor of postoperative mortality and should be considered in the selection of surgical approach and management strategy for patients in need of standard and transcatheter aortic valve replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 22 publications
3
53
0
1
Order By: Relevance
“…This interplay between MR and residual AR in patients undergoing TAVR has been previously suggested (4) and also has been reported for surgical prosthetic heart valves(37,38). Nonetheless, the clinical relevance of differences in MR changes over time remains to be determined.…”
supporting
confidence: 65%
“…This interplay between MR and residual AR in patients undergoing TAVR has been previously suggested (4) and also has been reported for surgical prosthetic heart valves(37,38). Nonetheless, the clinical relevance of differences in MR changes over time remains to be determined.…”
supporting
confidence: 65%
“…The overall incidence of PVL post-TAVR ranges between 50% and 85%, which is significantly higher than what has been observed in SAVR, reported between 1% and 47.6%, with only 4.2% consisting of more than mild PVL. 14 Although the majority of post-TAVR PVL is mild (7.8-40.8%), moderate (5-37.9%) and severe (0.5-13.6%) PVL occur frequently. 1,2,6,8,10,11,13,[15][16][17][18][19][20][21][22][23][24][25][26] The largest meta-analysis of TAVR outcomes estimates the incidence of residual moderate or severe aortic regurgitation after TAVR to be 7.4%.…”
Section: Definition and Incidencementioning
confidence: 94%
“…The benchmark for paravalvular regurgitation after conventional valve replacement is high and should be considered when evaluating patients for transcatheter or sutureless valve replacement. (J Thorac Cardiovasc Surg 2015;-: [1][2][3][4][5][6][7][8][9] PVR in valve replacement surgery. Incidence of PVR at discharge and in follow-up including and excluding subacute bacterial endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A recent study found an incidence of PVR 2þ or greater in 4.2% of patients with surgical AVR. 8 Rarely did these studies separate infectious causes of PVR from noninfectious PVR, possibly a more appropriate comparison with PVR in TAVR. Recent literature on TAVR reports historical PVR rates in surgical AVR between 1% and 47%, perhaps significantly higher than the contemporary surgical PVR frequency.…”
Section: Central Messagementioning
confidence: 99%